Managing Organizational Communication in Tourism Industry. The Case of Kosovo - MEHA, Arbresha; ZEQIRI, Flamur (Journal of Environmental Management and Tourism, 2021)
The main purpose of this paper is to explore the definition of the tourism industry and to examine the forms and importance of managing organizational communication in the tourism industry. Organizational communication deals with the interaction, coordination between individuals in a group, company, or organization. Effective communication results in problem-solving and decision-making at the organizational level. Communication skills regulate behavior and create motivation among people. Motivation is an important part and factor of behavior and should be part of a communication process. To successfully manage communication network and be effective, it must include training and guidance, and that the information is accurate in a timely manner in order to resolve and prevent potential conflicts. The tourism industry brings many economic benefits, jobs and raises the image of the country, and through tourism the country can be recognized and promoted by attracting foreign tourists. The tourism industry is the combination of all sectors related to tourism, a combination of hotels and facilities for accommodation, entertainment, business, and other purposes, so it interacts with many sectors of the economy.